GMAT Question of the Day: Daily via email | Daily via Instagram New to GMAT Club? Watch this Video

 It is currently 31 May 2020, 00:22

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# If y(x - 1) = z then x =

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics
Author Message
TAGS:

### Hide Tags

Math Expert
Joined: 02 Sep 2009
Posts: 64248
If y(x - 1) = z then x =  [#permalink]

### Show Tags

29 Jul 2019, 22:53
00:00

Difficulty:

5% (low)

Question Stats:

97% (00:31) correct 3% (01:38) wrong based on 32 sessions

### HideShow timer Statistics

If y(x - 1) = z then x =

A. y - z
B. z/y + 1
C. y(z - 1)
D. z(y - 1)
E. 1 - zy

_________________
Senior Manager
Joined: 28 Jun 2019
Posts: 469
Re: If y(x - 1) = z then x =  [#permalink]

### Show Tags

30 Jul 2019, 01:52
YX-Y=Z
==》YX=Y+Z
==》X=Y+Z/Y= 1+ Z/Y
Option B

Posted from my mobile device
_________________
Always waiting
GMAT Club Legend
Joined: 11 Sep 2015
Posts: 4879
GMAT 1: 770 Q49 V46
Re: If y(x - 1) = z then x =  [#permalink]

### Show Tags

30 Jul 2019, 05:05
Top Contributor
Bunuel wrote:
If y(x - 1) = z then x =

A. y - z
B. z/y + 1
C. y(z - 1)
D. z(y - 1)
E. 1 - zy

Another approach....

GIVEN: $$y(x - 1) = z$$

Divide both sides by y to get: $$x-1=\frac{z}{y}$$

Add 1 to both sides to get: $$x=\frac{z}{y}+1$$

Cheers,
Brent
_________________
Test confidently with gmatprepnow.com
Target Test Prep Representative
Status: Founder & CEO
Affiliations: Target Test Prep
Joined: 14 Oct 2015
Posts: 10602
Location: United States (CA)
Re: If y(x - 1) = z then x =  [#permalink]

### Show Tags

05 Aug 2019, 18:17
Bunuel wrote:
If y(x - 1) = z then x =

A. y - z
B. z/y + 1
C. y(z - 1)
D. z(y - 1)
E. 1 - zy

yx - y = z

yx = z + y

x = (z + y)/y

x = z/y + y/y

x = z/y + 1

Alternate Solution:

y(x - 1) = z

x - 1 = z/y

x = z/y + 1

_________________

# Scott Woodbury-Stewart

Founder and CEO

Scott@TargetTestPrep.com
202 Reviews

5-star rated online GMAT quant
self study course

See why Target Test Prep is the top rated GMAT quant course on GMAT Club. Read Our Reviews

If you find one of my posts helpful, please take a moment to click on the "Kudos" button.

Re: If y(x - 1) = z then x =   [#permalink] 05 Aug 2019, 18:17

# If y(x - 1) = z then x =

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics

 Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne